The Epicardium in the Embryonic and Adult Zebrafish - Marina Peralta; Juan Manuel González-Rosa; Inês Joao Marques; Nadia Mercader (Journal of Developmental Biology, 2014)
The epicardium is the mesothelial outer layer of the vertebrate heart. It plays an important role during cardiac development by, among other functions, nourishing the underlying myocardium, contributing to cardiac fibroblasts and giving rise to the coronary vasculature. The epicardium also exerts key functions during injury responses in the adult and contributes to cardiac repair. In this article, we review current knowledge on the cellular and molecular mechanisms underlying epicardium formation in the zebrafish, a teleost fish, which is rapidly gaining status as an animal model in cardiovascular research, and compare it with the mechanisms described in other vertebrate models. We moreover describe the expression patterns of a subset of available zebrafish Wilms’ tumor 1 transgenic reporter lines and discuss their specificity, applicability and limitations in the study of epicardium formation.